THU0283 Two Year Follow-Up on Biologics Use in 13 Centers - Data from the International Registry for Biologics in SLE (IRBIS). (23rd January 2014) - van Vollenhoven, R.; Mild, M.; Jacobsen, S.; Wallace, D. J.; Hanley, J. G.; Petri, M. A.; Bernatsky, S. R.; Bae, S.-C.; Ramos-Casals, M.; Garcia-Hernandez, F.; Ayala-Guiterrez, M. D. M.; Ramsey-Goldman, R.; et al.
Abstract : Background: Only one biologic agent has been approved for use in SLE, but some are used off-label in various settings. To obtain information systematically regarding this, members of the SLICC group initiated the International Registry for Biologics in SLE (IRBIS). The entire registry contains data from 28 centers. Objectives: To analyse the use of biologics in SLE, and assess the results achieved over the first two years after initiation. Methods: IRBIS investigators provided retrospective data on all patients treated with a biologic for SLE at their center. Standardized case report forms were used to collect demographic, disease-specific and treatment data at the time of biologic initiation and at yearly follow-ups. Here, data is presented from 13 reporting centers for which two-year follow-up data were available. Results: Based on the complete data set, 455 patients were treated with rituximab (84%), belimumab (10%), epratuzumab (5%), and anti-tumor necrosis factor agents (abatacept, etanercept and adalimumab, each <1%). The major organ manifestations leading to biologic treatment were lupus nephritis (LN, 44%), hematological (17%), musculoskeletal (16%), skin disease (10%), CNS (4%) and other (9%). Reasons for choosing the biologic were disease-control (73%), steroid-sparing (5%) or both (23%). At biologic initiation mean disease duration (±SD) was 9.5±7.9 years, and mean age was 42.2±12.5. Most patients (91%) were female. Prior to biologic treatment, most patients (91%) had been treated with one or more immunosuppressants (IS). Just over half (57%) had used 1-2 IS drugs, 21% had used three, and 13% had used 4-6 IS drugs. At two-year follow-up (n=120), SLE disease activity (SLEDAI) and glucocorticoid (GC) dose was significantly lower versus baseline (mean±SD SLEDAI: 9.4±5.3 to 3.1±2.5; mean±SD GC dose: 10.7±13.9 to 4.8±5.9 mg; paired analyses, p<0.0001 for both comparisons). SLICC damage-index remained unchanged. At baseline, concomitant GC was used in 91% of patients compared to 61% at follow-up. There was a slight trend to decreasing use of IS drugs from baseline (57%) to follow-up (51%). In almost half of patients (48%) there was at least one adverse event reported over the indicated follow-up period. However, only 5% were related to the biologic agent. Serious adverse events were serious opportunistic infections (n=4), posterior reversible encephalopathy syndrome (PRES, 3), serious allergic reactions (4), serious infections (6) and death (6). Conclusions: Rituximab was the biologic used most commonly in this multi-center international lupus cohort and was used for a range of SLE manifestations. At two-year follow-up both lupus activity and concomitant glucocorticoid dosage had decreased. Over time, GC use decreased, with a trend for a decrease in IS drug use as well. Disclosure of Interest: None Declared